THE RELATIONSHIP OF MAKING AUDIO VISUAL MEDIA WITH STUDY MOTIVATION IN PSYCHOLOGICAL COURSES: HUBUNGAN PEMBUATAN MEDIA AUDIO VISUAL DENGAN MOTIVASI BELAJAR PADA MATA KULIAH PSIKOLOGI - Nunik Esti Utami; Saifullah; Eka Jaya Putera Utama; Basuki Wibowo (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
Learning that is carried out by students is using the cooperative learning model by making creative media to support the percentage of students in the classroom. Some students do not understand in making Audio Visual learning media, by using audio visual media it is expected that student learning motivation will arise. Quantitative descriptive method is used when it aims to describe or explain events or an incident that is happening at the present time in the form of meaningful numbers. With a number of subjects of 26 students. Interlationsship studies. Testing for normality uses the Kolmogorov-Smirnov analysis technique and for calculations using the SPSS 16.0 for Windows program. The data is said to be normally distributed if the significance value is greater than 0.05 at the significance level α = 0.05. The linearity results above indicate that the significance level is 0.588> 0.05; so that the two variables can be said to be linear. Based on the results of the hypothesis is the hypothesis in this study is